Metabolic Parameters in Patients with Prader-Willi Syndrome and DiGeorge Syndrome with Respect to Psychopathological Manifestation - Krefft M (Dove Medical Press, 2020)
Maja Krefft,1 Dorota Frydecka,1 Robert Śmigiel,2 Błażej Misiak3 1Department of Psychiatry, Wroclaw Medical University, Wroclaw, Poland; 2Department of Pediatrics, Division of Pediatrics and Rare Disorders, Wroclaw Medical University, Wroclaw, Poland; 3Department of Genetics, Wroclaw Medical University, Wroclaw, PolandCorrespondence: Maja KrefftDepartment of Psychiatry, Wroclaw Medical University, 10 Pasteur Street, Wroclaw 51-367, PolandTel +48509457693Email maja.krefft@gmail.comPurpose: The purpose of our study was to compare the metabolic parameters in two genetic syndromes with a proven high risk of developing psychiatric comorbidities. These comorbidities, especially mood and psychotic disorders, may be associated with a risk of obesity, type 2 diabetes and other components of metabolic syndrome regardless of antipsychotic treatment.Patients and Methods: Two groups of children diagnosed with Prader - Willi syndrome (PWS) (n = 20) and DiGeorge syndrome (DGS) (n = 18), aged 7– 18 years, were enrolled. Behavioral symptoms and co-occurring psychopathological symptoms were assessed using the Child Behavior Checklist (CBCL). The levels of following biochemical parameters were measured: glucose, insulin, high-sensitivity C-reactive protein, total cholesterol, low- and high-density lipoproteins (LDL and HDL), triglycerides and non-HDL cholesterol. Additionally, the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) was calculated.Results: There were significantly higher levels of insulin and non-HDL in patients with PWS compared to those with DGS. The scores of four CBCL subscales (social problems, thought problems, delinquent behavior and aggressive behavior) were significantly higher in PWS patients. Higher scores of the CBCL-thought problems were associated with significantly higher levels of insulin as well as HOMA-IR.Conclusion: Patients with PWS seem to be more prone to develop subclinical metabolic dysregulation, in terms of elevated non-HDL levels and insulin levels, compared to DGS patients. Altered insulin sensitivity, present in both groups, even though it is not a specific risk factor, might be related to thought problems associated with psychosis.Keywords: rare disease, metabolic dysregulation, lipid, psychosis, psychopathology